2000
DOI: 10.1034/j.1399-3038.2000.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway nitric oxide in infants with acute wheezy bronchitis

Abstract: Concentrations of nitric oxide (NO) in exhaled air are increased in children and adults with asthma, and NO measurements are used as a non-invasive marker to monitor airway inflammation in these patients. To define the role of NO in infants with acute wheezy bronchitis, we measured nasal and end-tidal NO concentrations in 17 infants with acute virus-associated wheezy bronchitis, in 22 term infants without respiratory disease, and in nine premature infants. Nasal NO measurements were performed with an olive pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 33 publications
(44 reference statements)
5
51
0
Order By: Relevance
“…For infants slightly older than our study participants, there has not been any difference between strictly oral or nasal eNO [50]. Although mixed eNO has been shown in infants to differentiate health from a variety of airway diseases [27,50,51], this must be considered before using our normative values as reference.…”
Section: Limitations and Open Questionsmentioning
confidence: 99%
“…For infants slightly older than our study participants, there has not been any difference between strictly oral or nasal eNO [50]. Although mixed eNO has been shown in infants to differentiate health from a variety of airway diseases [27,50,51], this must be considered before using our normative values as reference.…”
Section: Limitations and Open Questionsmentioning
confidence: 99%
“…Therefore, though FeNO appears to reflect eosinophilic bronchial inflammation early in life, the current evidence is insufficient to state that FeNO performed in children at 0 to 4 years of age predicts a diagnosis of asthma at age 5 and above. However; future studies (one is ongoing 176 ) may demonstrate otherwise. The strength of evidence assessment is summarized in Table 6.…”
Section: Key Pointsmentioning
confidence: 99%
“…175 The fourth study is an ongoing prospective cohort that has reported only preliminary findings not relevant to this question; final results will be relevant because the study will attempt to develop a prediction rule based on data from demographics, history, specific IgE, FeNO and peak expiratory flow. 176 Another study was only published as an abstract. In a population-based birth cohort, FeNO was measured in 234 healthy term infants aged 5 weeks during quiet tidal breathing in unsedated sleep.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, measurements based on quiet tidal breathing usually result in higher proportions of children being able to perform the maneuver satisfactorily than spirometry as a forced expiratory maneuver, as illustrated in a review on lung function tests in preschool children with cystic fibrosis (16). Until now, multiple-breath eNO (eNOmb) measurements have mostly been performed in infants and toddlers (17)(18)(19)(20)(21). Despite requiring less cooperation beyond infancy, criteria for standardization of eNOmb measurements are not yet included in the current ERS/ATS guidelines due to methodological issues (9).…”
mentioning
confidence: 99%